2004
DOI: 10.1111/j.1443-1661.2004.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a lead shield for laparoscopic detection of the sentinel lymph nodes in gastric cancer

Abstract: Background: Accurate staging of lymph node metastasis by sentinel node biopsy is easily achieved in conventional open gastric surgery. Staging is not easily achieved in laparoscopic surgery, however, because of the technical difficulty in identifying sentinel nodes. We developed a laparoscopic method that involves lead shielding for detection of sentinel nodes in gastric cancer and examined the efficacy of this method. Methods: Laparoscopic sentinel node biopsy was performed in 18 patients with early gastric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Similarly, Wang et al did not obtain a satisfactory result: a higher pooled identification rate and sensitivity in laparotomy but a higher pooled accuracy rate and negative predictive value in laparoscopy . Therefore, more studies are needed to confirm if there are any exaggerated merits of open surgery when combined with dye‐guided detection or overcritical drawbacks of laparoscopic surgery while combined with radio‐guided procedures in previous studies …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Wang et al did not obtain a satisfactory result: a higher pooled identification rate and sensitivity in laparotomy but a higher pooled accuracy rate and negative predictive value in laparoscopy . Therefore, more studies are needed to confirm if there are any exaggerated merits of open surgery when combined with dye‐guided detection or overcritical drawbacks of laparoscopic surgery while combined with radio‐guided procedures in previous studies …”
Section: Discussionmentioning
confidence: 97%
“…41 Therefore, more studies are needed to confirm if there are any exaggerated merits of open surgery when combined with dye-guided detection or overcritical drawbacks of laparoscopic surgery while combined with radio-guided procedures in previous studies. 46,[94][95][96] Previous studies reported that, even with an FN SLN, metastatic non-SLN was always situated in the same SLN basin in GC. 95,[97][98][99][100] Therefore, the LBD seemed safer than the pick-up method, and it should be proposed as a standard technique to detect nodal metastases.…”
Section: It Was Recently Reported In Cochrane Database Of Systematicmentioning
confidence: 99%
“…Japan (5) Isozaki et al 17 Prospective Clinical (6) South Korea (1) Nimura et al 18 Prospective Kim et al 19 Prospective Tanaka et al 20 Prospective Yasuda et al 21 Prospective Osaka et al 22 Prospective 2005…”
Section: Identification Of Slnsmentioning
confidence: 97%
“…In 9 (21%) of those 43 studies, the authors adopted laparoscopic or laparoscopic-assisted procedures. 16,21,23,34,37,42,46,47,53 The remaining four (9%) studies were constructed with amalgamated patient subsets of open and laparoscopic treatment. 18,35,49,55 It is unsurprising that reports from the early 2000s show that attempts of SNNS at that time were undertaken during open surgery.…”
Section: Patient Selection and Surgical Managementmentioning
confidence: 99%